The Politics of Waqf Practice in Pesantren Kyai Families in Bangkalan Madura, Indonesia - Choiri, Muttaqin; Ardyansyah, Farid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Waqf Law mandates that waqf management is expected to sustain and improve the ummah's economy, but many waqf practices are not carried out according to procedures, such as changing Nazirs without coordinating with the Indonesian Waqf Board, which is done by many Kyai in Bangkalan Regency. Waqf Core Principles is an initiative effort that aims to provide a description of the position and role of waqf management and supervision systems in economic development programs and as a methodology on the core principles of management and supervision. This research uses a qualitative approach. Data were obtained from waqf managers in Islamic boarding schools in Bangkalan Regency, targeting effective waqf management in Waqf Core Principals, using componential analysis with Atlas.ti. The research findings show that the practice of waqf in Islamic boarding schools in Bangkalan Regency is more of a formal practice as a requirement for obtaining assistance and the like, including the waqf management structure revolving around close family circles, while in terms of supervision, the government is passive in waiting if there are problems and adjusting the budget in socialization and supervision activities. Building awareness of the utilization of waqf assets can be done through structured counseling through existing instructors in each sub-district by building synergies with pesantren, as educational, religious and social institutions that are trusted to be at the forefront and pilot of waqf development.